Kesantunan Berbahasa Pengamat Politik Rocky Gerung dalam Mengkritik Pemerintah dalam Kanal Youtube - Khairurrizki Khairurrizki; Agustina Agustina (Jurnal Bahasa dan Sastra, 2023)
This research was motivated by the delivery of criticism towards the government which is considered less polite by some circles. The purpose of this study is to explain the politeness in the language of RG political observers when criticizing the government. This type of research is qualitative research. The method used in this research is descriptive method. The main instrument is the researcher himself. The data of this research is in the form of speeches by political observers of the RG which contain criticism of the government. The data source for this research is the RG YouTube channel. The data collection technique used is the observation and note taking technique. The data validation technique used in this study is triangulation. Technical data analysis is carried out by analyzing data according to the theoretical studies used to answer research questions that have been formulated. The research results show that. First, GM political observers in criticizing the government tend to use speech acts of direct criticism, although they sometimes use indirect criticism. Second, in criticizing RG, the dominant uses the maxim of praise, then agreement, and wisdom. However, RG tends to violate the politeness principles, especially the maxims of praise. This is because the criticism given tends to be direct without paying attention to the face of the speech partner or being criticized by RG.